2006
DOI: 10.1177/030802260606901206
|View full text |Cite
|
Sign up to set email alerts
|

The Student's Perspective on What Makes an Exceptional Practice Placement Educator

Abstract: A Canadian occupational therapy organisation has recognised exceptional student supervision for practice placements by giving awards since 1990. Students have voluntarily nominated their practice placement educator by writing a statement outlining why the educator deserved the award. To determine the student's perspective on what qualities make an exceptional educator, the researchers analysed the 103 nominations using thematic analysis. Four primary themes emerged from the data, namely creating a positive lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 15 publications
3
34
0
2
Order By: Relevance
“…This included provision of an organised orientation program and clear expectations about what was required of students. This was consistent with the findings of Kirke et al (2007) and Mulholland, Derdall and Roy (2006), who found that a welcoming environment involved both an affective quality and an organisational one involving preparation such as gathering resources, and time spent clarifying learning needs, setting up learning experiences, making sufficient time to direct the student's learning and assessment (Kirke et al, 2007;Mulholland et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This included provision of an organised orientation program and clear expectations about what was required of students. This was consistent with the findings of Kirke et al (2007) and Mulholland, Derdall and Roy (2006), who found that a welcoming environment involved both an affective quality and an organisational one involving preparation such as gathering resources, and time spent clarifying learning needs, setting up learning experiences, making sufficient time to direct the student's learning and assessment (Kirke et al, 2007;Mulholland et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Approachability and friendly communication has been found (Bonello, 2001;Hummell, 1997;Kirke et al, 2007;Mulholland et al, 2006) to be supportive of students' learning. The balance between supervision and autonomy was raised both by participants in this and previous studies (Bonello, 2001;French & Hughes, 2007;Kirke et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As described by Rodger et al (in press) and Mulholland et al (2006), the practice educators in this study sought to create a supportive environment and an open relationship to make students feel safe to "have a go" in unfamiliar clinical situations and learn from their mistakes. This may be a more difficult task and require more attention for OCP approaches in which there are fewer predetermined procedures, such as standardised assessments or pre-planned, directed therapy sessions, than in other therapy approaches.…”
Section: Discussionmentioning
confidence: 99%
“…1), are strongly interconnected as emerged also in other studies (Mulholland et al, 2006;Papastavrou et al, 2010;Skaalvik et al, 2011). If the organization of clinical teaching fosters the partnership between clinical teachers and students (Saarikoski and Leino-Kilpi, 2002), the students will advance in understanding their professional identity (Andrew, 2012;Brennan and Timmins, 2012) and will be motivated to foster professional values (Keeling and Templeman, 2013).…”
Section: Discussionmentioning
confidence: 89%